Predicting Preeclampsia Pregnancy Termination Time Using sFlt-1 - Tanaka, Hiroaki; Tanaka, Kayo; Takakura, Sho; Enomoto, Naosuke; Ikeda, Tomoaki (Frontiers in Medicine, 2022)
Background The aim of this study was to determine the usefulness of placental growth factor (PlGF) and soluble fms-like tyrosine kinase-1 (sFlt-1) in predicting the time for pregnancy termination in pregnant women with known preeclampsia (PE) onset. Methods Forty-four pregnant women diagnosed with PE (22 weeks 0 days to 33 weeks 6 days gestation) were included in this study. The levels of sFlt-1 and PlGF, and the sFlt-1/PlGF ratio were compared between the women that delivered in <24 h (T group) and those that delivered in more than 24 h (P group), and between women that delivered in <1 week (T group) and those that delivered in more than 1 week (P group). Cutoff values were calculated for the three markers that were the most significantly correlated with predicting pregnancy termination at <24 h and <1 week. Results Among sFlt-1, PlGF, and sFlt-1/PlGF, sFlt-1 was the most significantly associated with the timing of pregnancy termination. sFlt-1 cutoff values of 8682.1 pg/ml (AUC 0.71; 95%Cl, 0.5191–0.9052) and 7,394.5 pg/ml (AUC 0.78; 0.78, 95%Cl, 0.6394–0.9206) for delivery in <24 h and delivery within 1 week, respectively, were important predictive values. The positive predictive value for delivery within 24 h was 43.9%, with a sensitivity of 72.3% and specificity of 69.0%, when sFlt−1 was <8,682 pg/ml. A sFlt-1 level of 7,394 pg/ml or greater would result in delivery within 1 week, with a positive predictive value of 67.2%; the sensitivity was 79.0% and specificity was 72.0%. Conclusion This study showed that sFlt-1 may be effective in predicting the timing of pregnancy termination. However, the number of cases was small and, thus, the results were not definitive. This finding should be researched further in order to predict the optimal timing of pregnancy termination in PE to reduce severe maternal complications.